A red phosphorus flame-retardant polyamide composite material and preparation method and application thereof
By adding metazirconic acid or zirconium anhydride to the red phosphorus flame retardant polyamide composite material, the corrosion problem of the material under the action of heat, oxygen and water is solved, and the low corrosion and high toughness are achieved, and the flame retardant performance and high CTI value of the material are maintained.
Patent Information
- Application Number
- CN202310438660.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-04-23
AI Technical Summary
The existing red phosphorus flame-retardant PA66 materials are prone to corrosion under the action of heat, oxygen and water, resulting in a decrease in product quality and shortened service life, and it is difficult to take into account both low corrosion and high toughness.
By adding metazirconic acid or zirconium anhydride to the red phosphorus flame retardant polyamide composite material, the phosphate is coordinated with its strong coordination ability to reduce the formation of phosphine and metal corrosion, while inhibiting the oxidation of red phosphorus, maintaining the flame retardant performance and high CTI value of the material.
It has achieved low corrosion, good toughness, red phosphorus flame-retardant polyamide composite materials, and high CTI values, meeting the needs of application scenarios such as electronic and electrical components.
Smart Images

Figure BDA0004193058520000021 
Figure BDA0004193058520000031 
Figure BDA0004193058520000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of engineering plastics, and more specifically to a red phosphorus flame retardant polyamide composite material and a preparation method and application thereof. Background Art
[0002] Polyamide has very excellent mechanical properties, wear resistance, heat resistance, solvent resistance, etc., and is widely used in machinery manufacturing, power tools, electronic appliances, transportation and other fields.
[0003] PA66 is one of the most common polyamides. Since the flame retardant property of PA66 itself is only V-2, its application in the field of electronic appliances is limited, so flame retardant modification is required. As a halogen-free flame retardant, red phosphorus has the advantages of little impact on mechanical properties, better electrical properties and smoke density than halogen flame retardant systems, light density, and high cost performance. Therefore, red phosphorus is often used as a flame retardant in PA66. However, since red phosphorus itself is prone to produce phosphine under the action of heat, oxygen, and water, and then turns into oxygen-containing acids, it corrodes metals in close contact, affects the conductivity of the product, causes abnormal product quality, and shortens the service life of the product. This is also one of the main reasons why some industries ban red phosphorus materials.
[0004] In order to solve the corrosion problem of red phosphorus flame retardant PA66, the following three solutions are commonly proposed: (1) reducing the generation of phosphine and oxygen-containing acids, such as the patented red phosphorus flame retardant reinforced thermoplastic polyamide composition and the patented method for preparing microencapsulated ultrafine red phosphorus, which use microencapsulated red phosphorus for modification, and reduce the contact of red phosphorus with water and oxygen by coating the red phosphorus. However, in the actual production process, it undergoes twin-screw shearing, heating and single-screw injection molding, etc., which makes it difficult to solve the generation of phosphine and oxygen-containing acids from the source, and thus corrosion is inevitable; (2) by weakening screw shearing or introducing nitrogen during the production process for protection, such as the patented acid-free, high electrical insulation red phosphorus flame retardant reinforced nylon and its preparation method, which avoids contact with oxygen by introducing nitrogen, thereby reducing corrosion to metals, but the production process is too complicated and expensive; (3) using adsorbents, fillers, and metal oxides for absorption and inhibition, such as the patented Reduction of phosphine relaease in plastic articles comprising red phosphorus uses activated carbon and zeolite to adsorb phosphine, reduce the generation of oxygen-containing acids, and reduce corrosion, but these adsorbents greatly damage the toughness of the material; a patented low-odor red phosphorus flame-retardant reinforced polyamide material absorbs phosphine by adding diatomaceous earth, a patented use of iron oxide in eliminating the irritating odor in red phosphorus flame-retardant nylon reduces the generation of phosphine by adding iron oxide, and a patented low-corrosion, low-odor glass fiber reinforced red phosphorus flame-retardant nylon 66 composite material and preparation method thereof reduces the generation of phosphine by adding hydroxide, talc, magnesium oxide, calcium oxide, etc., but these fillers, adsorbents, metal oxides, and hydroxides have a significant negative impact on the mechanical properties of the material, especially the toughness, affecting its application in high-toughness products.
[0005] Therefore, it is necessary to solve the problem that the current red phosphorus flame retardant PA66 has difficulty in achieving both low corrosion and high toughness. Summary of the invention
[0006] The primary purpose of the present invention is to overcome the problem that the current red phosphorus flame-retardant PA66 is difficult to balance low corrosion and high toughness, and to provide a red phosphorus flame-retardant polyamide composite material. The red phosphorus flame-retardant polyamide composite material has the characteristics of low corrosion, good toughness, red phosphorus is not easily oxidized, and a high CTI value.
[0007] A further object of the present invention is to provide a method for preparing the red phosphorus flame retardant polyamide composite material.
[0008] A further object of the present invention is to provide an application of the red phosphorus flame retardant polyamide composite material in the preparation of electronic and electrical components.
[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0010] A red phosphorus flame-retardant polyamide composite material comprises the following components in parts by weight:
[0011]
[0012] The zirconium compound is at least one of metazirconic acid and zirconic anhydride.
[0013] The mass percentage of PA66 in the red phosphorus flame-retardant polyamide composite material of the present invention is generally above 15%.
[0014] The inventor of the present invention has found through multiple studies that metazirconic acid has a strong coordination ability for phosphate. When metazirconic acid is added to the red phosphorus flame retardant polyamide composite material, when red phosphorus reacts to become phosphine under the action of heat, oxygen and water and further transforms into phosphate, metazirconic acid can coordinate the phosphate, reduce the content of free phosphate, thereby reducing the metal corrosion of the material and the release of phosphine; and metazirconic acid has no obvious negative impact on the toughness of the red phosphorus flame retardant polyamide composite material, so that the red phosphorus flame retardant polyamide composite material maintains good toughness, which meets the requirements of application scenarios. In addition, metazirconic acid forms a complex after coordinating the phosphate. On the one hand, the complex can inhibit the oxidation of red phosphorus, so that the red phosphorus flame retardant polyamide composite material maintains good flame retardant properties. Specifically, the discoloration of the red phosphorus flame retardant polyamide composite material under the double 85 test is greatly improved, indicating that the oxidation of red phosphorus is well suppressed; on the other hand, the complex formed after coordination can keep the red phosphorus flame retardant polyamide composite material with a high CTI value. Zirconic anhydride is hydrolyzed to form metazirconic acid. Adding zirconic anhydride to red phosphorus flame-retardant polyamide composites can produce an effect similar to that of metazirconic acid.
[0015] That is, the red phosphorus flame-retardant polyamide composite material of the present invention has the characteristics of low corrosivity, good toughness, red phosphorus not being easily oxidized and high CTI value.
[0016] Preferably, the red phosphorus flame retardant polyamide composite material comprises the following components in parts by weight:
[0017]
[0018] Preferably, the zirconium compound is metazirconic acid.
[0019] Optionally, the relative viscosity of the PA66 is 2.36-2.7, and the terminal amino group concentration is 36.6-82 mmol / Kg. Preferably, the relative viscosity of the PA66 is 2.65-2.7, and the terminal amino group concentration is 39.5-82 mmol / Kg.
[0020] By selecting PA66 within the relative viscosity and terminal amino group concentration range, the resulting red phosphorus flame-retardant polyamide composite material releases less phosphine and has lower corrosion to metals.
[0021] The terminal amino group concentration of PA66 of the present invention can be measured by potentiometric titration.
[0022] Red phosphorus can be added in the form of red phosphorus masterbatch or red phosphorus powder. When added in the form of red phosphorus masterbatch, the weight fraction of red phosphorus in the red phosphorus flame retardant polyamide composite material is obtained by multiplying the weight fraction of red phosphorus masterbatch by the percentage content of red phosphorus in the red phosphorus masterbatch.
[0023] Preferably, the red phosphorus is added in the form of red phosphorus masterbatch.
[0024] More preferably, the red phosphorus content of the red phosphorus masterbatch is 40-65wt%.
[0025] Optionally, the reinforcing material is at least one of glass fiber, carbon fiber, aramid fiber or ceramic fiber.
[0026] More preferably, the reinforcing material is glass fiber.
[0027] Further preferably, the cross section of the glass fiber is elliptical, and the ratio of the maximum diameter to the minimum diameter of the ellipse is (2.5-4):1.
[0028] When the cross section of the glass fiber is elliptical, the obtained red phosphorus flame-retardant polyamide composite material releases less phosphine and has higher notched impact strength.
[0029] Optionally, the toughening agent is at least one of a copolymer of ethylene and acrylic acid or a polyolefin elastomer grafted with maleic anhydride.
[0030] Preferably, the toughening agent is a copolymer of ethylene and acrylic acid.
[0031] In order to obtain more excellent or new properties, the red phosphorus flame retardant polyamide composite material of the present invention may further include other conventional processing aids in the art, and the type and amount of each processing aid may be selected and adjusted according to actual needs.
[0032] Preferably, the red phosphorus flame retardant polyamide composite material further comprises 0.2 to 2 parts of a processing aid.
[0033] More preferably, the processing aid is at least one of an antioxidant or a lubricant.
[0034] Optionally, the antioxidant is at least one of antioxidant 1098, antioxidant 245, antioxidant 1790 or antioxidant 445.
[0035] Optionally, the lubricant is at least one of a fatty acid ester lubricant, a metal soap lubricant, a fatty alcohol lubricant or a fatty acid lubricant.
[0036] The preparation method of the red phosphorus flame retardant polyamide composite material comprises the following steps:
[0037] The components except red phosphorus and the reinforcing material are mixed and melted, and then the red phosphorus and the reinforcing material are added from a side feed port, extruded and granulated to obtain the red phosphorus flame-retardant polyamide composite material.
[0038] Red phosphorus can be added in the form of red phosphorus masterbatch or red phosphorus powder. The main difference between the two is that when adding red phosphorus masterbatch, it is not necessary to create a nitrogen atmosphere at the side feed port; while when adding red phosphorus powder, it is necessary to create a nitrogen atmosphere at the side feed port to avoid the red phosphorus powder from directly contacting the air and causing fire or explosion hazards. It is a common practice in this field to adjust the process (whether to create a nitrogen atmosphere) according to the different forms of red phosphorus addition.
[0039] The application of the above red phosphorus flame-retardant polyamide composite material in the preparation of electronic and electrical components is also within the protection scope of the present invention.
[0040] Preferably, the electronic and electrical component is a connector, a circuit breaker or a contactor.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The red phosphorus flame-retardant polyamide composite material of the invention has the characteristics of low corrosivity, good toughness, red phosphorus being difficult to be oxidized and high CTI value. DETAILED DESCRIPTION
[0043] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0044] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0045] PA66-1#: viscosity is 2.7, terminal amino content is 47mmol / kG, PA66 EP-158, Zhejiang Huafeng Group; the viscosity is calibrated according to GB / T 12006.1-2009 Plastic Polyamide Part 1, and the following PA66 is the same.
[0046] PA66-2#: viscosity 2.65, terminal amino content 82mmol / kG, PA66 EP158NH, Zhejiang Huafeng Group;
[0047] PA66-3#: viscosity 2.7, terminal amino content 39.5mmol / kG, PA66 50BWFS, ASCEND Group;
[0048] PA66-4#: viscosity 2.38, terminal amino content 49.2mmol / kG, PA66 21ZLV, ASCEND Group;
[0049] PA66-5#: viscosity 2.57, terminal amino content 36.6mmol / kG, PA66 88X, ASCEND Group;
[0050] PA66-6#: viscosity 2.62, terminal amino content 40.3mmol / kG, PA66 EPR27, Shenma Group;
[0051] PA66-7#: viscosity 2.36, terminal amino content 40.2mmol / kG, PA66 EPR24, Shenma Group;
[0052] Red phosphorus masterbatch 1#: HDFRMB40, red phosphorus content 40%, Yunnan Haoding New Materials Co., Ltd.;
[0053] Red phosphorus masterbatch 2#: HDFRMB65BK, red phosphorus content 65%, Yunnan Haoding New Materials Co., Ltd.;
[0054] Red phosphorus powder 3#: encapsulated, red phosphorus content more than 85%, FSE-M1001, Shaoyang Fusen Flame Retardant Material Co., Ltd.
[0055] Reinforcement material 1#: Glass fiber: Glass fiber ECS301CL-3, the cross section of the glass fiber is circular, Chongqing International Composite Materials Co., Ltd.;
[0056] Reinforcement material 2#: Glass fiber: Glass fiber ECS301HP-3-M2.5, the cross section of the glass fiber is elliptical, and the ratio of the maximum diameter to the minimum diameter of the cross section is 2.5:1, Chongqing International Composite Materials Co., Ltd.;
[0057] Reinforcement material 3#: Glass fiber: Glass fiber ECS301HP-3-M4, the cross section of the glass fiber is elliptical, and the ratio of the maximum diameter to the minimum diameter of the cross section is 4:1; Chongqing International Composite Materials Co., Ltd.;
[0058] Toughening agent 1#: PC-28, maleic anhydride grafted POE, Foshan Nanhai Bochen Polymer New Materials Co., Ltd.;
[0059] Toughener 2#: Nucrel 3990, ethylene and acrylic acid copolymer, Dow Chemical;
[0060] Zirconium compound 1#: metazirconic acid, Aladdin Reagent Co., Ltd.;
[0061] Zirconium compound 2#: zirconic anhydride, Yixing Xinxing Zirconium Industry Co., Ltd.;
[0062] Processing aid 1#: antioxidant 1098, commercially available;
[0063] Processing aid 2#: lubricant, hexadecanol hexadecanoate, commercially available;
[0064] Carbon black: BLACK PEARLS M717, Cabot, USA.
[0065] Unless otherwise specified, the components (such as processing aids) selected in the parallel examples and comparative examples are all the same commercially available products.
[0066] The red phosphorus flame retardant polyamide composite materials provided in the embodiments and comparative examples of the present invention were tested for performance according to the following test methods:
[0067] (1) Izod notched impact strength: tested in accordance with ISO 180:2019;
[0068] (2) Flame retardant performance: tested according to UL 94, sample size 125×13×1.6mm;
[0069] (3) Phosphine release: ① Equipment: drying dish (caliber 300 mm), Dräger phosphine tester, stopwatch; ② Continuously inject at 285°C, 280°C, 275°C, and 270°C, take samples at intervals of 40 seconds, continuously inject 20 molds, take the sample strips from the 21st mold, put them in a drying dish, seal it, press the stopwatch to start the timing, and take the reading at 5 minutes; ③ Phosphine release = reading of the detector / mass of the sample strip (ppm / kg).
[0070] (4) Characterization of phosphorus corrosion: ① Equipment: thermal aging oven, wide-mouth bottle, test tube with a diameter of 12 mm and a length of 100 mm, analytical balance, inductively coupled atomic emission spectrometer ICP, tweezers; ② Take 50 grams of particles and place them in a 500 ml wide-mouth bottle, then take a copper sheet with a specification of 80 mm*10 mm*1.0 mm, insert it into the particles, and the length of the exposed part is 40 mm. Fill the test tube with 8 ml of deionized water, put the test tube into the wide-mouth bottle, seal it, and then place the wide-mouth bottle at 85°C for 3 days, take out the copper sheet, visually observe the corrosion effect, and record the corrosion level;
[0071] Copper sheet corrosion level 1: There is basically no corrosion or rust on the copper sheet;
[0072] Copper corrosion level 2: 1 / 3 of the copper sheet has corrosion and rust.
[0073] Copper corrosion level 3: 2 / 3 of the copper sheet is corroded and rusted;
[0074] Copper corrosion level 4: More than 2 / 3 of the copper sheet is corroded and rusted.
[0075] (5) Double 85 color change test: The red phosphorus flame retardant polyamide composite material is made into a color plate, and its initial LAB value is tested using a colorimeter. The color plate is then placed under 85°C and 85% humidity conditions for 1000 hours, and its LAB value is measured again to calculate △E.
[0076] (6) CTI test: According to the IEC-60112 standard: Determination of the tracking index and comparative tracking index of solid insulating materials, the CTI test is performed on the samples.
[0077] The preparation process of the red phosphorus flame retardant polyamide composite material provided by each embodiment of the present invention (except Example 17) and each comparative example is as follows: weigh the dried PA66, toughening agent, zirconium compound, and processing aid (if any) according to the weight ratio, and mix them evenly in a high-speed mixer to obtain a mixture; select a twin-screw extruder with double-side feeding, and the feeding port includes a main feeding port, a first side feeding port (i.e., a side feeding port away from the head), and a second side feeding port (i.e., a side feeding port close to the head); feed the mixture from the main feeding port, feed the red phosphorus masterbatch from the first side feeding port, and feed the reinforcing material from the second side feeding port (the aspect ratio of the twin-screw extruder is 48:1, the temperature is set at 270-290°C, and the speed is set at 600RPM); after melt blending, cooling, air drying, and granulation, the red phosphorus flame retardant polyamide composite material is obtained.
[0078] Example 17 uses red phosphorus powder instead of red phosphorus masterbatch, and the preparation process of its red phosphorus flame-retardant polyamide composite material is basically the same as that of Example 1. The difference is that: based on the preparation process of Example 1, nitrogen is introduced into the first side feeding port so that the red phosphorus powder is fed in a nitrogen atmosphere to avoid hidden dangers such as fire and explosion.
[0079] Examples 1 to 22
[0080] Examples 1 to 22 provide a series of red phosphorus flame retardant polyamide composite materials, whose formulas are shown in Table 1, Table 2 and Table 3.
[0081] Table 1 Formulas of Examples 1 to 9 (parts by weight)
[0082]
[0083] Table 2 Formulas of Examples 10 to 17 (parts by weight)
[0084]
[0085]
[0086] Table 3 Formulations of Examples 18 to 22 (parts by weight)
[0087]
[0088] Comparative Example 1
[0089] This comparative example provides a red phosphorus flame-retardant polyamide composite material, the formula of which is different from that of Example 1 in that: zirconium compound 1# is not added.
[0090] Comparative Example 2
[0091] This comparative example provides a red phosphorus flame-retardant polyamide composite material, the formula of which is different from that of Example 1 in that the amount of zirconium compound 1# added is 0.05 parts by weight.
[0092] Comparative Example 3
[0093] This comparative example provides a red phosphorus flame-retardant polyamide composite material, the formula of which is different from that of Example 1 in that zirconium compound 1# is replaced with carbon black.
[0094] The properties of the red phosphorus flame retardant polyamide composite materials of each embodiment and comparative example were tested according to the above-mentioned test method. The test results are shown in Table 4.
[0095] Table 4 Performance test results of red phosphorus flame retardant polyamide composite materials of various embodiments and comparative examples
[0096]
[0097]
[0098] From Table 4, we can see that:
[0099] The phosphine release of the red phosphorus flame-retardant polyamide composite materials of Examples 1 to 22 is less than 98ppm / Kg, the copper sheet corrosion level is 1 to 3, and the change of the LAB value of the double 85 color change test is less than 0.81, indicating that the red phosphorus flame-retardant polyamide composite material of the present invention has low corrosiveness and red phosphorus is not easily oxidized; the cantilever beam notched impact strength of the red phosphorus flame-retardant polyamide composite materials of Examples 1 to 22 is greater than 15.2kJ / m2, and the flame retardant level reaches V-1 level or above, indicating that the red phosphorus flame-retardant polyamide composite material of the present invention maintains good toughness and flame retardant properties, and can meet the use requirements of various scenarios. In addition, the CTI values of the red phosphorus flame-retardant polyamide composite materials of Examples 1 to 22 are all above 550V, indicating that the red phosphorus flame-retardant polyamide composite material of the present invention has a high CTI value.
[0100] Comparative Example 1 did not add zirconium compounds, and the phosphine release of the obtained red phosphorus flame retardant polyamide composite material was too high, the copper sheet corrosion grade was level 4, and the change value of the LAB value of the double 85 color change test was 2.3, indicating that its red phosphorus was easily oxidized, highly corrosive, and its CTI value was also low. The amount of zirconium compound added in Comparative Example 2 was too small, and the phosphine release of the obtained red phosphorus flame retardant polyamide composite material was too high, and the copper sheet corrosion grade was level 4, indicating that its red phosphorus was easily oxidized and highly corrosive. Comparative Example 3 did not add zirconium compounds, but added carbon black, and the change value of the LAB value of the double 85 color change test was 1.73, which was at a relatively high level, indicating that its red phosphorus was also easily oxidized, and the toughness and CTI value were also poor relative to Example 1.
[0101] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A red phosphorus flame retardant polyamide composite material, characterized in that: The composition comprises the following components in parts by weight: PA66 13.9~70.89 parts, 4 to 8.45 parts of red phosphorus, 10 to 35 parts of reinforcing material, 6-20 parts of toughening agent, 0.1 to 1 part of zirconium compound; The zirconium compound is at least one of metazirconic acid or zirconic anhydride; The mass percentage of PA66 in the red phosphorus flame-retardant polyamide composite material is more than 15%.
2. The red phosphorus flame retardant polyamide composite material according to claim 1, characterized in that: The zirconium compound is metazirconic acid.
3. The red phosphorus flame retardant polyamide composite material according to claim 1, characterized in that: The relative viscosity of the PA66 is 2.65-2.7, and the terminal amino group concentration is 39.5-82 mmol / Kg.
4. The red phosphorus flame retardant polyamide composite material according to claim 1, characterized in that: The red phosphorus is added in the form of red phosphorus masterbatch.
5. The red phosphorus flame retardant polyamide composite material according to claim 1, characterized in that: The reinforcing material is at least one of glass fiber, carbon fiber, aramid fiber or ceramic fiber.
6. The red phosphorus flame retardant polyamide composite material according to claim 5, characterized in that: The cross section of the glass fiber is oval.
7. The red phosphorus flame retardant polyamide composite material according to claim 1, characterized in that: The toughening agent is a copolymer of ethylene and acrylic acid.
8. The red phosphorus flame retardant polyamide composite material according to claim 1, characterized in that: The red phosphorus flame retardant polyamide composite material also includes 0.2 to 2 parts of processing aid.
9. The method for preparing the red phosphorus flame retardant polyamide composite material according to any one of claims 1 to 8, characterized in that: The steps include: The components except red phosphorus and the reinforcing material are mixed and melted, and then the red phosphorus and the reinforcing material are added from a side feed port, extruded and granulated to obtain the red phosphorus flame-retardant polyamide composite material.
10. Use of the red phosphorus flame retardant polyamide composite material according to any one of claims 1 to 8 in the preparation of electronic and electrical components.
Citation Information
Patent Citations
Bio-based PA56T and PA56 composite material and preparation method thereof
CN110903644A
Cited By
Flame-retardant nylon-SPS composition as well as preparation method and application thereof
CN122080629A